2013
DOI: 10.1016/j.tet.2013.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of benzopyranopyrrolidines via 1,3-dipolar cycloaddition of nonstabilized azomethine ylides with 3-substituted coumarins

Abstract: a b s t r a c tA three-component reaction of 3-substituted coumarins with N-alkyl-a-amino acids and aldehydes gave 1-benzopyrano[3,4-c]pyrrolidines as a result of a 1,3-dipolar cycloaddition of an intermediate nonstabilized azomethine ylide at the double bond of the coumarin system in moderate to good yields. In most cases, high regio-and stereo-selectivity of the [3þ2] cycloaddition was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…After cooling, the precipitate was filtered off, washed with ethanol, and finally dried. peak), 363 (M + À 1, 73), 241 (12), 108 (19), 107 (14).…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…After cooling, the precipitate was filtered off, washed with ethanol, and finally dried. peak), 363 (M + À 1, 73), 241 (12), 108 (19), 107 (14).…”
Section: Tablementioning
confidence: 99%
“…The 1,3‐dipolar cycloaddition of azomethine ylide with dipolarophile is the key of many research groups. 1,3‐Dipolar cycloaddition is potential synthetic applications of many compounds such as incorporation of pentafluorosulfanyl group into isoxazoles and isoazolines , lactams, indolizidines, alkaloids , dispirooxindolopyrrolidines , pyrrolines, pyrrolidines , benzopyranopyrrolidines , pyrrolidinyl oxindoles , and dispirooxindolecyclo[pyrrole(1,2‐c)thiazole‐6,5̍‐thiazolidine] derivatives . In the present research, we have examined a new example of a 1,3‐dipolar cycloaddition between azomethine ylide with dipolarophile with a highly electron rich alkene.…”
Section: Introductionmentioning
confidence: 99%
“…Conjugate addition reactions to 3-diethylphosphonocoumarin 1a using asymmetric nonstabilized azomethine ylides were investigated by Moshkin et al [55,56]. The developed approach for the synthesis of products 28 and 29 utilized as starting material the in situ formed ylide derived from cyclohexanone and N-methylglycine (Scheme 29).…”
Section: Synthesis and Some Reactions Of Dialkyl 2-oxo-2h-1-benzopmentioning
confidence: 99%
“…In previous publications using coumarins and chromones we observed that nonstabilized azomethine ylides reacted poorly with weak electronwithdrawing or sterically hindered dipolarophiles. 16e, 23 We envisaged that the reactions with more active fluorenone and (trifluoromethyl)phenylketone may produce the corresponding oxazolidines in good yield.…”
Section: Introductionmentioning
confidence: 99%